The Impact of Dynamic Capabilities on Digital Transformation: A Study in “A” Conglomeration’s Non-Bank Financial Institutions - Fiona Fiona; Aloysius Anandyo Pambudi; Samuel Dicsky Wahyudi; Mira Maulida (Return : Study of Management, Economic and Bussines, 2026)
This study investigates how dynamic capabilities influence digital transformation within the Non-Bank Financial Institutions (NBFIs) sector of the “A” conglomerate. In Indonesia’s financial industry, digital transformation has become a strategic priority, but organizations still face several obstacles, including high technology investment costs, difficulties in adapting to digital systems, and regulatory compliance requirements. The research applies the Dynamic Capabilities (DC) framework together with the Technology-Organization-Environment (TOE) framework to analyze how both internal and external factors affect the implementation of digital transformation in NBFIs. The results show that technological capability and innovation play a major role in driving digital transformation, while organizational capability strengthens innovation development. In contrast, ecosystem capability and governance, risk, and compliance (GRC) factors do not demonstrate a significant influence. Overall, the findings offer useful insights for NBFIs in designing and implementing more effective digital transformation strategies.